Strategy for Implementing Artificial Based Learning Models in Improving Learning Quality - Sintha Wahjusaputri; Bunyamin Bunyamin; Tashia Indah Nastiti; Evi Sopandi (Dinamika Pendidikan, 2023)
This research seeks to develop and design solutions for artificial intelligence-based learning models to improve learning quality in higher education. The qualitative technique was used in this study, which was completed in three steps: data collection, analysis, and conclusion. To establish the best approach, this study employs validity testing and a SWOT analysis. this research resulting 10 strategies in the implementation of an Artificial intelligent based learning model, namely: Develop a curriculum in accordance with technological developments in Industry 4.0; Establish or establish a special technology development Lab in the field of artificial intelligence and other fields; Creating and using learning media based on bolted intelligence; Conduct regular evaluations by universities/faculties regarding the use or development of artificial intelligence technology; Conducting outreach regarding the importance of data privacy; Provide training for both students and lecturers on artificial intelligence; Provide socialization about entrepreneurship, especially in the field of artificial intelligence; Designing university regulations related to infrastructure to be able to support the development of artificial intelligence; Provide career and talent consulting assistance for students; provide socialization on professional ethics to students and lecturers.